Representação feminina no Legislativo amazonense: perfil e atuação das parlamentares na 19ª Legislatura (2019-2022) da ALEAM - Conceição, Aline Paiva (Brasil, 2024)
This study arises from the empirical perception of gender inequality in politics in Amazonas, verified by the small presence of women in the state parliament. In this sense, the work proposes to dissertate on female representation in politics in Amazonas, through a sociopolitical analysis of the profile and performance of the women’s caucus that composed the 19th Legislature (2019-2022) of ALEAM, identifying who they are and how they acted in their mandates. This is, therefore, a qualitative-quantitative research focused on three analytical aspects: biographical profile, political action and legislative production. The methodologies used were prosopography and data survey obtained from the Legislative Process Support System - SAPL. It is inferred that the women’s caucus is governed by local political elites, reproducing patriarchal and clientelistic values. Furthermore, although women's agendas have increased with the presence of more women in Parliament, the women's agenda is predominantly conservative, with few nuances of progressivism and disdain for women belonging to minority groups.